2002
DOI: 10.1128/aac.46.3.882-883.2002
|View full text |Cite
|
Sign up to set email alerts
|

Antitrypanosomal Activities of Tryptanthrins

Abstract: New drugs and molecular targets are needed against Trypanosoma brucei, the protozoan that causes African sleeping sickness. Tryptanthrin (indolo[2,1-b]quinazoline-6,12-dione), a traditional antifungal agent, and 11 analogs were tested against T. brucei in vitro. The greatest activity was conferred by electron-withdrawing groups in the 8 position of the tryptanthrin ring system; the most potent compound had a 50% effective concentration of 0.40 M.Members of the Trypanosoma brucei species are flagellated protozo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 9 publications
(7 reference statements)
2
65
0
Order By: Relevance
“…40 Tryptanthrin 44 (indolo [2,1-b]quinazoline-6,12-dione) is unusual in that its synthesis was described 50 years before it was discovered in a number of plant species. Scovill et al 41 The unsubstituted compounds were weakly active (IC 50 = 23 and 40 µM for 44 and 45 respectively). The antitrypanosomal activity was markedly improved by the presence of an electron-withdrawing group (halogen or nitro) at position 8 of the (aza)tryptanthrin ring system: the most active analog of the series, 4-aza-8-bromotryptanthrin 46, was up to 100 times more active than the unsubstituted parent compound 45 (IC 50 = 0.4 µM).…”
Section: Alkaloidsmentioning
confidence: 97%
See 1 more Smart Citation
“…40 Tryptanthrin 44 (indolo [2,1-b]quinazoline-6,12-dione) is unusual in that its synthesis was described 50 years before it was discovered in a number of plant species. Scovill et al 41 The unsubstituted compounds were weakly active (IC 50 = 23 and 40 µM for 44 and 45 respectively). The antitrypanosomal activity was markedly improved by the presence of an electron-withdrawing group (halogen or nitro) at position 8 of the (aza)tryptanthrin ring system: the most active analog of the series, 4-aza-8-bromotryptanthrin 46, was up to 100 times more active than the unsubstituted parent compound 45 (IC 50 = 0.4 µM).…”
Section: Alkaloidsmentioning
confidence: 97%
“…The antitrypanosomal activity was markedly improved by the presence of an electron-withdrawing group (halogen or nitro) at position 8 of the (aza)tryptanthrin ring system: the most active analog of the series, 4-aza-8-bromotryptanthrin 46, was up to 100 times more active than the unsubstituted parent compound 45 (IC 50 = 0.4 µM). 41 Camptothecin 47, a pentacyclic alkaloid from Camptotheca acuminata (Nyssaceae), is a well known antitumor agent and a specific inhibitor of human DNA topoisomerase I. Bodley et al have shown that 47 also inhibits the nuclear and mitochondrial topoisomerase I of T. b. brucei thus blocking DNA replication and inducing the death of bloodstream trypomastigotes (IC 50 = 1.6 µM). 42 In a study of a series of camptothecin analogs, the 9-substituted-10,11-methylenedioxy derivatives were significantly more active on T. b. brucei bloodstream trypomastigotes than the parent compound and retained as intracellular target the parasites' topoisomerase I.…”
Section: Alkaloidsmentioning
confidence: 99%
“…30 The formation of intermediate azomethines (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) disappearance of peaks at 1680-1695 cm -1 for -CHO and 3380-3440 cm -1 for -NH 2 of starting materials and at the same time appearance of band at 1610-1635 cm -1 which is characteristic for -CH=N group. 31 The formation of title compounds (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were confirmed by the disappearance of the absorption maxima at 3330-3400 cm -1 , which are ascribed to the vibrations of NH group of the indole ring; at the same time the appearance of a new maximum at 1360-1380 cm -1 , which is characteristic for indolo [1,2-c] quinazoline ring with a tertiary nitrogen atom, appears. 32 The exhibited chemical shifts obtained from 1 H NMR spectra of compounds 1-20 supported the proposed structures of the compounds.…”
Section: Chemistrymentioning
confidence: 93%
“…Screening results are summarized in Table 1. The antimicrobial screening revealed that some of the compounds (15)(16)(17)(18)(19)(20) showed high activity against all bacterial and fungal strains. In particular, bis-indolo [1,2-c] quinazolines (19 and 20) showed excellent activity against all tested strains.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation